Endometrial cancer prognosis in women with endometriosis and adenomyosis: A retrospective nationwide cohort study of 40 840 women. Issue 9 (27th December 2021) - Hermens, Marjolein; van Altena, Anne M.; van der Aa, Maaike; Bulten, Johan; van Vliet, Huib A. A. M.; Siebers, Albert G.; Bekkers, Ruud L. M.
Abstract: We aim to compare endometrial cancer survival in women with or without histological proven endometriosis or adenomyosis. We identified all women with endometrial cancer between 1990 and 2015 from the Netherlands Cancer Registry (NCR). Data were linked to the Dutch pathology database (PALGA) to select all women with histological proven endometriosis/adenomyosis. Overall survival was compared between women with endometrial cancer with or without endometriosis/adenomyosis. We used multivariable Cox proportional hazard analysis to estimate hazard ratios (HRs). We included 1701 women with endometrial cancer and endometriosis/adenomyosis, of whom 1236 (72.7%) women had adenomyosis, 320 (18.8%) had endometriosis and 145 (8.5%) had both. We compared these women to 39 139 women with endometrial cancer without endometriosis/adenomyosis. Women in the combined endometriosis/adenomyosis cohort were younger at endometrial cancer diagnosis, had earlier disease stage, more often had endometrioid endometrial cancer and low grade tumors. The 5‐year survival rate in the combined endometriosis/adenomyosis cohort was 84.8% (95% CI 84.6‐88.1) and 71.6% (95% CI 71.1‐72.0) in the nonendometriosis/adenomyosis cohort. Univariable analysis resulted in a crude HR of 0.63 (95% CI 0.59‐0.69). Significant confounding factors were age, stage, cancer subtype, histological grading, surgery and chemotherapy rate. Correction for these confounders resulted in a HR of 0.98 (95% CI 0.90‐1.06). Including endometriosis/adenomyosis status as a categorical factor resulted in similar HRs. In conclusion, women with endometrial cancer and histologically proven endometriosis/adenomyosis have a better overall survival when compared to women with endometrial cancer without endometriosis/adenomyosis. This better survival was correlated to stage, grade, age and histological subtype, but not to the presence of endometriosis/adenomyosis. Abstract : What's new? Whether women with adenomyosis and endometrial cancer have better overall survival rates compared to women with endometrial cancer without adenomyosis remains unclear. In this nationwide study involving more than 40, 000 women with endometrial cancer, women with endometrial cancer and histologically proven endometriosis or adenomyosis were found to survive longer after cancer diagnosis than women without endometriosis/adenomyosis. Women with endometriosis/adenomyosis were diagnosed with endometrial cancer at a younger age and had tumor characteristics, including stage, grade, and histological subtype, that generally are associated with more favorable cancer outcome. Following correction for confounders, endometriosis/adenomyosis status was not independently prognostic for endometrial cancer.